The role of mobile banking application architecture on the intention to use Sharia Banking: The mediating role of digital service familiarity - Hafiez Sofyani; Rizka Amalia; Dara Alifa Fajriati Thamrin; Nguyen Tran Thai Ha; Mohammed Saleh Al-Maghrebi (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study investigates the impact of the application architecture of mobile banking on users' intention to use Sharia banking through digital service familiarity as a mediator. The study employed a survey questionnaire distributed online to users of Sharia banking in Indonesia, specifically targeting those who use mobile banking. To ensure the validity of the questionnaire, consultations with four experts and a pilot study were conducted. 316 respondents are obtained but only 280 valid data are able to be analyzed. Hypothesis testing was carried out using structural equation modelling with partial least squares. The results indicate that application architecture of mobile banking and digital service familiarity enhance users' intention to use Sharia banking services. Additionally, digital service familiarity mediate the relationship between application architecture and users' intention to use Sharia banks. The findings suggest that Sharia banking practitioners should enhance application architecture and increase user familiarity with digital services to enhance users' intention to use sharia bank. This research add the literature of the mediating role of digital service familiarity on the relationship between application architecture and users' intention to use Sharia banking services. Recommendation for future research is that researchers may further develop the research model by including additional variables such as trust, service quality, or user satisfaction, as well as conducting cross-country comparisons to obtain a more comprehensive understanding of the factors influencing Sharia banking adoption.